Delayed postoperative hemorrhage (DEPOH) in an Irish Wolfhound with the SERPINF2 c.605 T/T genotype: case description and variant prevalence across dog breeds - Court, Michael H.; Hardy, Melissa; Forbes, Keith R.; Yang, Hong; Jimenez, Tania Perez (Frontiers in Veterinary Science, 2025)
IntroductionDelayed postoperative hemorrhage (DEPOH) is a life-threatening complication of major surgical procedures in Greyhounds affecting up to 26–30% of dogs. DEPOH has also been reported in Scottish Deerhounds, but it is unclear whether any other breeds are affected. A genetic variant (c.605 C > T) was recently discovered in the SERPINF2 gene that is currently used as a biomarker for increased risk of DEPOH. The objective of this study was to provide the first report of DEPOH occurring in association with the SERPINF2 variant in an Irish Wolfhound. SERPINF2 variant prevalence was also surveyed across dog breeds to identify other breeds that may be at increased risk for DEPOH.MethodsCase history and medical records from the affected dog were reviewed. SERPINF2 genotypes were determined for this dog and for 63 different breeds (including 16 different sighthound breeds) using DNA samples from 4,044 pet dogs supplemented with publicly available genotype data.ResultsThe reported case was a 2-year-old healthy female Irish Wolfhound who underwent ovariohysterectomy and prophylactic gastropexy procedures without complication. Two days later extensive bruising was noted on the ventral abdomen that spread to the torso by day 4 when the dog collapsed and died. Necropsy revealed extensive external and internal bruising with free and clotted blood in the abdomen. All ligatures were intact, and no sources of bleeding were identified. Subsequent genotyping indicated that this case was homozygous for the SERPINF2 T/T high risk genotype. Greyhounds had the highest T/T genotype prevalence (29%), Irish Wolfhounds had the second highest prevalence (24%), and Scottish Deerhounds had the 8th highest prevalence (6%). Nine of 16 sighthound breeds had a T/T prevalence of at least 5%, while none of 47 non-sighthound breeds had a prevalence this high. Four non-sighthound breeds, including Shetland sheepdog, Newfoundland, English bulldog and French bulldog had a carrier (C/T or T/T) genotype prevalence over 20%.DiscussionThese results suggest that DEPOH could occur in most, but not all sighthound breeds. Some non-sighthound breeds might also be susceptible.